PERLINDUNGAN HUKUM BAGI PEKERJA PEREMPUAN YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA SEPIHAK OLEH PERUSAHAAN SAAT CUTI MELAHIRKAN - WIRADHARMA SUMERTAJAYA, I KETUT SATRIA; Dewi, Kadek Ary Purnama (Jurnal Yustitia, 2024)
Termination of employment is something that is avoided by workers in general, especially for female workers, of course it is very detrimental to their rights, which by nature have reproductive organs to give birth. However, in practice there are cases of female workers who experience termination of employment due to taking maternity leave. Based on this, the problem examined in this research concerns legal protection for female workers who experience unilateral termination of employment by the company during maternity leave. In this research the author uses a normative legal research method with a statute approach and a case approach, then the results found in this research are described descriptively The results of this research are that the laws and regulations in the field of employment regulate the right to obtain maternity leave as regulated in Article 82 of Law No. 13 of 2003 concerning Employment. The provisions of Article 153 paragraph (1) of Law no. 6 of 2023 states that companies are prohibited from terminating workers on the grounds of pregnancy, childbirth, miscarriage or breastfeeding their baby. If the company terminates the employment relationship unilaterally due to a female employee taking maternity leave, the termination of employment carried out for the reasons mentioned above is null and void and the Company is obliged to re-employ the employee concerned.